Restructuring of Finance Problem in Islamic Banks between Fiqh and the Fatwa of DSN MUI - Hasanudin Hasanudin; Viany Rahmawati (International Journal of Social Science and Religion (IJSSR), 2021)
The concept of problem solving on financing in the Fatwa of DSN-MUI No. 49/DSN-MUI/II/2005 regarding the conversion of the murabaha contract, it is different from the developed concept by the Fukaha. In the fatwa, the settlement of problematic murabaha financing can be done by rescheduling, reconditioning and restructuring. Meanwhile, fukaha saw the settlement of problematic financing can be done with two contracts, namely sulh and taflis. This research is library research, a form of research whose data sources are obtained from the library. The approach to this research uses a normative juridical method. The primary data source in this study is the DSN fatwa No. 49/DSN-MUI/II/2005 concerning the conversion of murabaha contracts. The results show that based on the perspective of Islamic law, the settlement of problematic financing based on the fatwa of the National Sharia Council No. 49/SSN-MUI/II/2005 on the conversion of murabaha contracts and some Fiqh opinions are not contradictory. Dispute resolution in the DSN-MUI fatwa in principle combines the techniques contained in akd sulh and taflis.